2010
DOI: 10.1007/s11162-010-9169-0
|View full text |Cite
|
Sign up to set email alerts
|

More Girls Go to College: Exploring the Social and Academic Factors Behind the Female Postsecondary Advantage Among Hispanic and White Students

Abstract: This study examines the female postsecondary advantage in matriculation among Hispanic and white youth with the goal of exploring whether social capital, in addition to academic performance and orientation, function similarly to help explain females' higher likelihood of college attendance for each group. Utilizing data from the Texas Higher Education Opportunity Project (THEOP), results indicate that girls' higher academic performance in high school is an important factor behind their subsequent gender advant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
56
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 43 publications
7
56
1
Order By: Relevance
“…Prior research has shown that, in the United States, female students take more rigorous high school science, technology, engineering, math and English courses (Peter and Horn 2005;Riegle-Crumb 2010) than do their male peers; the present study documents that music course-taking patterns also significantly vary with gender. I find that females are more likely to enrol in each type of music ensemble commonly offered in American high schools (band, orchestra and choir) than are their male counterparts, and this trend has been fairly stable for the past three decades.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Prior research has shown that, in the United States, female students take more rigorous high school science, technology, engineering, math and English courses (Peter and Horn 2005;Riegle-Crumb 2010) than do their male peers; the present study documents that music course-taking patterns also significantly vary with gender. I find that females are more likely to enrol in each type of music ensemble commonly offered in American high schools (band, orchestra and choir) than are their male counterparts, and this trend has been fairly stable for the past three decades.…”
Section: Discussionsupporting
confidence: 57%
“…Recent studies have shown that female students in the United States, though often underperforming male students in the economic and social outcomes of schooling (Weaver-Hightower 2003), typically outperform their male counterparts in many traditional academic indicators measured during schooling: reading achievement (Robinson and Lubienski 2011), secondary school graduation (Heckman and LaFontaine 2010), rigour of chosen secondary school courses (Peter and Horn 2005;Riegle-Crumb 2010), and postsecondary attendance, persistence and completion (Conger and Long 2010;Jacob 2002;Riegle-Crumb 2010).…”
mentioning
confidence: 99%
“…This advantage begins to manifest during primary education, where girls demonstrate more advanced social skills, better classroom behavior (Buchmann et al, 2008), and tend to be more academically engaged (Riegle-Crumb 2010) when compared to boys. Social capital (i.e., personal relationships with friends, parents and other adults) has historically been recognized as a female advantage (Reigle-Crumb, 2010).…”
Section: Gender Differences In College Readinessmentioning
confidence: 99%
“…Within higher education literature, there is a dearth of intersectionality research, which is not surprising since there is little empirical research on intersectionality in general (Hancock, 2007a). There is some research emerging regarding underrepresentation of men of color in higher education (e.g., College Board, 2010;Riegle-Crumb, 2010;Sáenz and Ponjuan, 2009), but this work fails to take account of the power structures that continue to favor men in society, and it tends to be primarily analyses of difference as opposed to illuminating hierarchical relationships. Institutional leaders and researchers may replicate these patterns as they conduct self-studies of their own campuses.…”
Section: Intersectionalitymentioning
confidence: 99%